Body mass index and the risk of disability retirement: a systematic review and meta-analysis. (29th August 2019) - Shiri, Rahman; Falah-Hassani, Kobra; Lallukka, Tea
Abstract : The aim of this study was to determine the associations of body mass index (BMI) with all-cause and cause-specific disability retirement. Literature searches were conducted in PubMed, Embase and Web of Science from their inception to May 2019. A total of 27 (25 prospective cohort and 2 nested case-control) studies consisting of 2 199 632 individuals qualified for a meta-analysis. Two reviewers independently assessed the methodological quality of the included studies. We used a random effects meta-analysis, assessed heterogeneity and publication bias, and performed sensitivity analyses. There were a large number of participants and the majority of studies were rated at low or moderate risk of bias. There was a J-shaped relationship between BMI and disability retirement. Underweight (hazard ratio (HR)/risk ratio (RR)=1.20, 95% CI 1.02 to 1.41), overweight (HR/RR=1.13, 95% CI 1.07 to 1.19) and obese individuals (HR/RR=1.52, 95% CI 1.36 to 1.71) were more commonly granted all-cause disability retirement than normal-weight individuals. Moreover, overweight increased the risk of disability retirement due to musculoskeletal disorders (HR/RR=1.26, 95% CI 1.15 to 1.39) and cardiovascular diseases (HR=1.73, 95% CI 1.24 to 2.41), and obesity increased the risk of disability retirement due to musculoskeletal disorders (HR/RR=1.66, 95% CI 1.42 to 1.94), mental disorders (HR=1.29, 95% CI 1.04 to 1.61) and cardiovascular diseases (HR=2.80, 95% CI 1.85 to 4.24). The association between excess body mass and all-cause disability retirement did not differ between men and women and was independent of selection bias, performance bias, confounding and adjustment for publication bias. Obesity markedly increases the risk of disability retirement due to musculoskeletal disorders, cardiovascular diseases and mental disorders. Since the prevalence of obesity is increasing globally, disease burden associated with excess body mass and disability retirement consequently are projected to increase. Review registration number : CRD42018103110.